A case of upper extremity thrombosis in patient with ulcerative colitis - İbrahim Halil Turkbeyler; Taner Babacan; M. Sait Dağ; Musa Aydınlı; Orhan Zengin; M. Akif Sarıca; Abdurrahman Kadayıfcı (Turkish Journal of Gastroenterology, 2019)
-